Increased levels of antibodies to synaptopodin and annexin 1 in patients with primary podocytopathies - Chebotareva, Natalia V.; Charionovskaya, Evgeniya A.; Biryukova, Evgenia A.; Vinogradov, Anatoliy A.; Alentov, Igor I.; Sergeeva, Natalia S.; Kononikhin, Alexey S.; Nikolaev, Evgeny N.; Moiseev, Sergey V. (Frontiers in Nephrology, 2024)
IntroductionCirculating anti-podocyte antibodies have been proposed as potential factors contributing to increased permeability in primary podocytopathies, such as Minimal Change Disease (MCD) and Focal Segmental Glomerulosclerosis (FSGS). The aim of the study was to to assess the levels of antibodies targeting synaptopodin and annexin 1 in the blood serum of patients diagnosed with nephrotic syndrome, with the aim of evaluating their potential utility in diagnosing primary podocytopathies and predicting therapeutic response.MethodsThe study included a total of 72 patients diagnosed with nephrotic syndrome, alongside 21 healthy subjects for comparison. Among the patients, 38 were diagnosed with FSGS, 12 with MCD, and 22 with MN. The levels of anti-synaptopodin and anti-annexin-1 antibodies were quantified using Enzyme-Linked Immunosorbent Assay.ResultsThe levels of antibodies to annexin 1 and anti-synaptopodin in the blood were found to be higher in patients diagnosed with MCD and FSGS compared to those with MN and healthy individuals. The elevated levels of antibodies to annexin 1 and synaptopodin showed area under the curve values of 0.826 (95% CI 0.732–0.923) and 0.827 (95% CI 0.741–0.879), respectively. However, a model incorporating both antibodies demonstrated higher sensitivity (80.9%) and specificity (81.3%) with an AUC of 0.859 (95% CI 0.760-0.957). Notably, serum levels of annexin 1 and anti-synaptopodin antibodies did not predict the response to prednisolone and/or CNI therapy.DiscussionLevels of antibodies targeting synaptopodin and annexin 1 were notably elevated in patients diagnosed with MCD and FSGS compared to those with MN and healthy controls. A panel comprising both antibodies demonstrated moderate to high sensitivity and specificity for diagnosis MCD or FSGS.